Sequential reciprocity in two-player, two-stage games: An experimental analysis - Dhaene, Geert; Bouckaert, Jan (Games and economic behavior, 2010)
We experimentally test Dufwenberg and Kirchsteiger's (2004) theory of sequential reciprocity in a sequential prisoner's dilemma and a mini-ultimatum game. Data on behavior and first- and second-order beliefs allow us to classify each subject's behavior as a material best response, a reciprocity best response, both, or none. We found that in both games the behavior of about 80% of the first movers was a material best response, a reciprocity best response, or both. The remaining 20% of first movers almost always made choices that were “too kind” according to Dufwenberg and Kirchsteiger's theory. Second-mover behavior, in both games, was in line with the predictions of the theory. We found first- and second-order beliefs to be unbiased in the sequential prisoner's dilemma, but biased in the mini-ultimatum game.